Pengayaan Kemampuan Pemasaran dan Kewirausahaan Peternak Domba Desa Sumbersawit Kabupaten Magetan - Lestari, Yetty Dwi; Wurjaningrum, Febriana; Auliandri, Tuwanku Aria; Sridadi, Ahmad Rizki; Kartika, Nurullaily; Barinta, Dunga Dwi (Penerbit Goodwood, 2025)
Purpose: This study aimed to enhance the entrepreneurial mindset and marketing skills of goat farmers in Sumbersawit Village, Magetan, through a community service initiative focused on digital marketing, social media use, and innovative livestock product management. Research methodology: Conducted in Sumbersawit Village, the program involved 20 goat farmers. This approach includes workshops on entrepreneurial motivation, digital marketing, and social media tools. Canva was introduced for content creation, and Instagram Ads for market reach expansion. Participants also engaged in hands-on sessions and designed campaigns on platforms such as Instagram and Tokopedia. Results: The program significantly improved participants’ entrepreneurial awareness and digital marketing competencies. Farmers successfully learned to create promotional materials using Canva and were able to broaden their reach through Instagram Ads. Around 80% of participants expressed interest in diversifying their livestock businesses, 60% planned to utilize goat waste for organic fertilizer, and 50% applied Instagram Ads to promote products online. Conclusions: This initiative boosted local entrepreneurship and digital literacy. Farmers demonstrated improved skills in using Canva and Instagram Insights to develop creative and impactful content. These changes are expected to increase income and expand customer reach. However, continued mentoring is essential for sustained application and innovation. Limitations: Limited digital exposure among the participants required extended training times. Additionally, the scope of the study —goat farmers in a single village—may limit its applicability to other agricultural sectors or regions. Contribution: This study offers a model for applying digital marketing to rural entrepreneurship. This highlights how accessible technologies can empower farmers and bridge rural-to-urban market gaps.